1991
DOI: 10.3354/meps076013
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of the planktonic stages of the American lobster Homarus americanus to thermal gradients, and ecological implications

Abstract: The behavioural responses of each planktonic stage (I to IV) of American lobster Homarus americanus to a thermal gradient were studied during complete day/night cycles using an experimental approach. The thermocline markedly influenced the vertical position of larvae of all stages, limiting their distribution to the upper part of the water column. In both absence or presence of a thermocline, older individuals (stages 111 & IV) were observed deeper in the water column than younger individuals (stages I & 11). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Cumulative size distributions and fitted logistic curves for lobsters collected by suction sampling (triangles) and collectors (squares) in four study areas where both methods were used at the same sites. Statistical analysis in Table III. Scheibling 1990; Raimondi 1991), the possibility should not be ruled out that postlarvae may concentrate in nurseries by a behavioural attraction to high densities of benthic conspecifics (Boudreau et al 1991;Burdett-Coutts 2010). Although sampling has been conducted for more than two decades at some of these locations Wahle et al 2009a), the present study represents the first sampling at others.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative size distributions and fitted logistic curves for lobsters collected by suction sampling (triangles) and collectors (squares) in four study areas where both methods were used at the same sites. Statistical analysis in Table III. Scheibling 1990; Raimondi 1991), the possibility should not be ruled out that postlarvae may concentrate in nurseries by a behavioural attraction to high densities of benthic conspecifics (Boudreau et al 1991;Burdett-Coutts 2010). Although sampling has been conducted for more than two decades at some of these locations Wahle et al 2009a), the present study represents the first sampling at others.…”
Section: Discussionmentioning
confidence: 99%
“…Forward 1990, Boudreau et al 1991 in order to maintain aerobic metabolism and high swimming activity, emphasizes their degree of thermal specialization. Behavioral responses to temperature can help larvae to control the experienced temperature regime only within limits (Kelly et al 1982, Sulkin 1984, Forward 1990, Shanks 1995, Gardner et al 2004), due to the large-scale nature of most physical drivers of SST fluctuations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Species from a wide variety of taxonomic groups including polychaetes, gastropods, bivalves, cirripedes, decapods, bryozoans, and echinoderms produce larvae whose vertical position in the water column has been shown to be influenced by vertical discontinuities in salinity and/or temperature (e.g. Harder 1968, Oshurkov et al 1982, Scrope-Howe & Jones 1986, Boudreau et al 1991, 1992, Thiebaut et al 1992, Raby et al 1994, Gallager et al 1996, Manuel et al 1996b. Although the scientific literature on the vertical distribution of invertebrate planktonic larvae in the water column in relation to vertical boundaries and water column mixing is substantial, very little work has been conducted to examine how these factors influence settlement of larvae [but see Boudreau et al (1992) who found that laboratory thermoclines significantly reduced the number of post-larval lobster Homarus amencanus settling in comparison with control columns of water with no temperature discontinuities].…”
Section: Introductionmentioning
confidence: 99%